Ultrasound guided transversus abdominis plane block versus intrathecal morphine for analgesia post caesarean section: which is better? - Aizatul Isla AL,; Nadia MN,; Wan Rahiza WM,; Azrin MA,; Thohiroh AR,; Nurlia Y, (Department of Surgery, UKM Medical Centre, 2013)
The tranversus abdominis plane (TAP) block for postoperative analgesia after caesarean section may confer potential benefits comparable to that of intrathecal opioids. We compared postoperative analgesia, and the incidence of nausea, vomiting, pruritus and sedation between the TAP block and intrathecal morphine (ITM) in patients undergoing Caesarean section. This was a prospective, randomised clinical study. Fifty American Society of Anaesthesiologists physical status I or II patients, planned for elective caesarean section under spinal anaesthesia, were randomly allocated to the TAP group (patients receiving spinal anaesthesia with bilateral TAP block without ITM) or ITM group (patients receiving spinal anaesthesia with ITM without a TAP block). Assessment for pain, postoperative nausea and vomiting, pruritus and sedation was done upon arrival and discharge from recovery, and at 6, 12 and 24 hours, postoperatively in the post natal ward. Results were analysed using analysis of variance (ANOVA). There was no pain at rest in either groups. Both groups experienced pain on movement at the 12th (p = 0.6) and 24th hour (p = 0.4). None of the patients in the TAP group experienced nausea, vomiting, pruritus or sedation. However, these incidences were found to be significantly higher in the ITM group. Ultrasound guided TAP block provided comparable postoperative analgesia to ITM without the side effects of the latter.